Immunization of Cattle With Recombinant Structural Ectodomains I and II of Babesia bovis Apical Membrane Antigen 1 [BbAMA-1(I/II)] Induces Strong Th1 Immune Response - Rittipornlertrak, Amarin; Nambooppha, Boondarika; Muenthaisong, Anucha; Apinda, Nisachon; Koonyosying, Pongpisid; Srisawat, Wanwisa; Chomjit, Paweena; Sangkakam, Kanokwan; Punyapornwithaya, Veerasak; Tiwananthagorn, Saruda; Yokoyama, Naoaki; Sthitmatee, Nattawooti (Frontiers in Veterinary Science, 2022)
Both strong innate and adaptive immune responses are an important component of protection against intraerythrocytic protozoan parasites. Resistance to bovine babesiosis is associated with interferon (IFN)-γ mediated responses. CD4+ T cells and macrophages have been identified as major effector cells mediating the clearance of pathogens. Previously, the apical membrane antigen 1 (AMA-1) was found to significantly induce the immune response inhibiting B. bovis merozoite growth and invasion. However, a detailed characterization of both humoral and cellular immune responses against the structure of B. bovis AMA-1 (BbAMA-1) has not yet been established. Herein, the present study aimed to express the recombinant BbAMA-1 domain I+II protein (rBbAMA-1(I/II)), which is the most predominant immune response region, and to characterize its immune response. As a result, cattle vaccinated with BbAMA-1(I/II) significantly developed high titters of total immunoglobulin (Ig) G antibodies and a high ratio of IgG2/IgG1 when compared to control groups. Interestingly, the BbAMA-1(I/II)-based formulations produced in our study could elicit CD4+ T cells and CD8+ T cells producing IFN-γ and tumor necrosis factor (TNF)-α. Collectively, the results indicate that immunization of cattle with BbAMA-1(I/II) could induce strong Th1 cell responses. In support of this, we observed the up-regulation of Th1 cytokine mRNA transcripts, including IFN-γ, TNF-α, Interleukin (IL)-2 and IL-12, in contrast to down regulation of IL-4, IL-6 and IL-10, which would be indicative of a Th2 cytokine response. Moreover, the up-regulation of inducible nitric oxide synthase (iNOS) was observed. In conclusion, this is the first report on the in-depth immunological characterization of the response to BbAMA-1. According to our results, BbAMA-1 is recognized as a potential candidate vaccine against B. bovis infection. As evidenced by the Th1 cell response, it could potentially provide protective immunity. However, further challenge-exposure with virulent B. bovis strain in immunized cattle would be needed to determine its protective efficacy.